Ultrasonic fatigue of laser beam powder bed fused metals: A state-of-the-art review. (April 2022) - Avateffazeli, Maryam; Haghshenas, Meysam
Highlights: A comprehensive review on ultrasonic fatigue response of additive manufactured materials. Extensive and critical review on the effect of additive manufacturing parameters on the very high cycle fatigue response. Critical review of the influence of microstructure inhomogeneity and the fractography aspects of additive manufactured metals in the ultrasonic fatigue testing. Abstract: Ultrasonic fatigue testing is a resourceful (time- and cost-saving) approach to assess the dynamic failure of materials in the gigacycle range (i.e., when the number of cycles to failure is beyond 10 million cycles). That is, ultrasonic fatigue is a popular tool of data collection that allows the testing of many cycles to occur in a small frame of time as the test specimen is cycled at an ultrasonic frequency of 20 kHz. The concept of very high cycle fatigue, which can be assessed through the ultrasonic fatigue testing method, has become an important point of learning for additively manufactured engineering structures and components that require long lives including automotive, aerial, and civil structures. Various additive manufacturing parameters contribute to the very high cycle fatigue response including the manufacturing process, material, size, and type of defects. This review aims at proving a background on the very high cycle fatigue, evaluating the governing mechanism of failure, and assessing the effect of manufacturing (i.e., laser beam powder bed fusion) parameters metallic materials. The special attention of this article is on the ultra-long fatigue response of laser powder bed fused metallic materials as the ultra-long fatigue domain is a less explored regime in revolutionary metal additive manufacturing. In terms of metal additive manufacturing, the focus of this paper is the laser beam powder bed fusion technique, being the most employed powder-based metal additive manufacturing process. The alloys that are reviewed in this article include AlSi10Mg, AlSi12, Ti6Al4V, stainless steel (i.e., 316L), and Ni superalloys (i.e., Inconel 718 and GH 4169) which are among the most popular and common alloys that are manufactured through the laser beam powder bed fusion process. This paper discusses the mechanism of crack initiation and characteristics (size, morphology, and location) of the defects in the microstructure that are responsible for the very high cycle fatigue failure. This paper extensively discusses the effect of additive manufacturing parameters on the very high cycle fatigue response of the mentioned alloys. Besides, the correlation between fractography aspects and stress intensity factors is discussed in this article. Finally, this review article provides an overview of future research trends and potential research opportunities of the VHCF of laser powder bed fused metallic materials.